PENERAPAN GOOD CORPORATE GOVERNANCE PADA PERBANKAN DI INDONESIA - SITI ARBAINA, ENDANG Siti (Jurnal Akuntansi AKUNESA, 2012)
Good corporate governance in banking is a bank governance that apply the principles oftransparency, accountability, responsibility, independency, and fairness. This article aimedto study The Implementation of Good Corporate Governance in Indonesian Banks. Goodcorporate governance is important because it can increase corporate profits andshareholders in the long term. But in Indonesian banking, implementation of good corporategovernance is weak, because law enforcement is not fully applicable to Indonesian banking.key words: good corporate governance, transparency, accountability, responsibility,independency, and fairness